(3GdJQJHjH aj Yde GdaQGFVs - (3TeS GdOjf eMeO Hf eMeO GdeGQOjfj GdTGaYjs; (3GdcdGFj , eMeO Hf TQa Hf YGOj GdbQTj GdRHjQj, TeS GdOjf , CHh YHO Gddg,J (B777 (3g` s ((3eMeO Hf eMeO GdbQdai s)
(3ChdgG (B:s
(3hHYO aEf cJGH GdeLehY ai Yde GdaQGFV JUfja GdTjN eMeO GdcdGYi s
(3BNQgG (B:s
(3agPG gh GdEjVGM YeG WdHJg Je cJGH GdJQJjH HMeOGddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3JQJjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B66s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1605s
Keywords: (3Yde GdaQGFVs